Qualitative and quantitative characteristic of angiogenesis in tumour transplantants under the influence of radiation therapy in rats. - Lysenko S.A. (Морфологія, 2007)
Qualitative and quantitative results of morphological investigation of experimental Geren’s tumour angiogenesis under the influence of radiation therapy according to intensive technique are presented. Microscopic and morphometric analysis of vascular channel in control and radiation tumour transplantants in 80-th an race rats of both sex are executed. Multivariance procedures of generalization linear models of system SAS are used because of statistic processing. General degeneration of parenchyma and vascular channel of tumours as well as signs of inhibitory influence of radiation on vessel development were revealed by means of light and electronic microscopy. In histomorphometric estimation of angiogenesis parameters tumours of the animals subjected to telegammatherapy showed considerably decreased density of vessel’s and relation area of vessel’s to area of tumour and essentially increased mean area of one vessel in comparison with tumours of the animals comprising control group. Such changes occur in dynamics, i.e. with growth of experimental tumours from the 12-th to 28-th day after their transplantation. Therefore, radiation therapy it is possible has to antiangiogenic action.